Investigation of Student Perspectives on Curriculum Needs for Autonomous Shipping - Tsvetkova, Anastasia; Morariu, Andrei-Raoul; Hellström, Magnus; Bolbot, Victor; Virtanen, Seppo (Sweden, 2025)
Digitalization and automation are reshaping the maritime industry, particularly through advancements in designing Maritime Autonomous Surface Ships (MASS) and the expected proliferation of autonomous shipping. These innovations are altering traditional roles in ship design, operations, and the maritime sector in general. The influx of cybersecurity, automation, and IT experts into the maritime sphere is necessary for MASS integration in logistic chains. This paper examines students’ perspectives on autonomous shipping, future job markets, and educational needs related to MASS. A survey of 159 students from Finnish universities studying in the fields of IT, maritime studies, engineering, naval architecture and business and law revealed significant interest in MASS-related education, driven by its anticipated impact on their careers. The study areas of interest include automation, computer engineering, general IT knowledge, Artificial Intelligence, and cybersecurity. The findings highlight the need for interdisciplinary curricula in MASS-related education, integrating technology, safety, legal, and business aspects of MASS.
Proceedings of the 20th International CDIO Conference